Triage systems: saturation in response to emergency rooms - Cubero Alpízar, Consuelo (2014)
Background. Strategies for the attention of users in emergency rooms in hospitals have become indispensable for the proper functioning of these services, due to increase in the growing demand for service delivery. In this context, a research project whose objective was to analyze the effectiveness of care systems worldwide hospital emergency arises.Method. All that was reviewed evidence published over the past 15 years, including staff observation applies to the system types triage and waiting times before the care and quality of care provided to the patient. The search strategy was used to identify clinical studies in different databases such as Pubmed, Cochrane library, EBSCO and google scholar.Result. Among the most relevant results identified saturation in emergency rooms as a real problem caused the increase in demand for such services globally, resulting in a lower quality of service provided and also an increase in mortality timeouts. Identified the random arrival care and structured, plus they are historically nurses which systems best meet the task does not compare.Conclusion.  It is urgent to review the classification systems of patients when they arrive at the emergency department of the hospital system, with the goal of triage systems adapt to the real needs of the country.